Effect of azithromycin on incidence of acute respiratory exacerbations in children with HIV taking antiretroviral therapy and co-morbid chronic lung disease: a secondary analysis of the BREATHE trial. (December 2021) - Price, Amy; McHugh, Grace; Simms, Victoria; Semphere, Robina; Ngwira, Lucky G; Bandason, Tsitsi; Mujuru, Hilda; Odland, Jon O; Ferrand, Rashida A; Rehman, Andrea M
Abstract: Background: In the BREATHE trial weekly azithromycin decreased the rate of acute respiratory exacerbations (AREs) compared to placebo among children and adolescents with HIV-associated chronic lung disease (CLD) taking antiretroviral therapy (ART). The aim of this analysis was to identify risk factors associated with AREs and mediators of the effect of azithromycin on AREs. Methods: The primary outcome of this analysis was the rate of AREs by study arm up to 49 weeks. We analysed rates using Poisson regression with random intercepts. Interaction terms were fitted for potential effect modifiers. Participants were recruited from Zimbabwe and Malawi between15 June 2016 and 4 September 2018. Findings: We analysed data from 345 participants (171 allocated to azithromycin and 174 allocated to placebo). Rates of AREs were higher among those with an abnormally high respiratory rate at baseline (adjusted rate ratio (aRR) 2.08 95% CI 1.10-3.95 p-value 0.02) and among those with a CD4 cell count <200 cells/mm 3 (aRR 2.71; 95% CI 1.27-5.76; p-value 0.008). We found some evidence for variation in the effect of azithromycin by sex (p-value for interaction=0.07); males had a greater reduction in the rate of ARE with azithromycin treatment than females. We found that azithromycin had a greater impact on reducing AREs in participants with chronic respiratory symptoms at baseline, those on 1st line ART, with a FEV1 score >-2 and participants without baseline resistance to azithromycin. However, there was no statistical evidence for interaction due to low statistical power. Interpretation: These may represent subgroups who may benefit the most from treatment with weekly azithromycin, which could help guide targeted treatment. Funding: There was no funding source for this post hoc analysis.